Coping strategies used by healthcare professionals during COVID-19 pandemic in Dubai: A descriptive cross-sectional study - Ahmad Hamdan; Jennifer Eastaugh; Johan Snygg; Jennifer Naidu; Ibtisam Alhaj (Narra X, 2023)
The coronavirus disease 2019 (COVID-19) pandemic has affected physical, social, and psychological well-being of all people, especially healthcare professionals (HCP), who are vulnerable to work-related stress. The aim of this study was to explore the effectiveness of coping strategies practiced by HCPs during the COVID-19 pandemic. A cross-sectional study was conducted in Mediclinic Welcare Hospital in Dubai during the pandemic between March 2020 and April 2021. The questionnaire was used to collect demographic data and validated Brief Coping Orientation to Problems Experienced (Brief-COPE) scales instrument was used to measure the coping strategies. A total 112 respondents were included in the final analysis consisting of physicians (11.6 %), nurses (60.7%), other clinical HCPs (24.1%), and non-clinical staff (7.2%). The common and effective coping strategies used by HCPs were within the problem-focused category. The female HCPs used multiple coping strategies to help them to manage their stress during COVID-19 pandemic. The nurses were more likely to report using emotional support as a coping strategy than doctors or other hospital staff members. Among 48.21% of the respondents that venting helped them release their feelings and distracted themselves through watching movies or television, reading, sleeping, or shopping. Moreover, 42.86% respondents found comfort in practicing religion and spiritual beliefs. Interestingly, the use of alcohol or other drugs was used as a coping mechanism during the pandemic, whereas emotional support and actions as well as taking other advice, were common strategies. Based on these data, healthcare institutions should consider a variety of support measures and programs for the mitigation of stress and negative emotional responses among HCPs during any future outbreaks or pandemics, such as providing access to mental health services, regular check-ins with colleagues or supervisors, peer support groups, educational resources on coping strategies, and paid time off for rest and recovery. Counseling and executive support services also could help staff to manage the mental health during future disasters.